Mapping Work–Family Conflict As An Indicator Of Work–Life Balance Among Indonesian Employees - Rahmat, Abdul; Syam, Rahmawati; Jufri, Muhammad; Zakiyah, Siti Nur’ainun (SOCIETIES: Journal of Social Sciences and Humanities, 2025)
This study aims to describe employees’ work–life balance profiles by measuring work–family conflict (WFC) using the unidimensional scale developed by Gutek et al. (1991). A total of 118 employees participated in an online survey. The results show that 70% of respondents were categorized as experiencing high WFC, 28% moderate WFC, and only 2% low WFC. Female employees and those who were married appeared more frequently in the moderate and high conflict categories, indicating a greater tendency to experience interrole strain compared to other groups. These findings highlight that work–family conflict remains a prominent and substantial experience among employees in the increasingly flexible and digitalized post-pandemic work context